Digital Literacy of Middle Class Muslims - Syifaul Arifin (Universitas Muhammadiyah Surakarta, 2017)
For a number of scholars, the emergence of middle class society is a considerable phenomenon. Moreover, it is linked to the transformation of education in the digital era. The middle class society has relatively established economic background, well-educated (senior secondary school and high education graduates), and high democratic consciousness. The number also flourished and thrives in line with national economic growth. Generally, they are the employees of private and government agencies, as well as entrepreneurs. In addition, they have appropriate access to information technology, indicated by the massive utilization of smartphones and social media for interaction. Nevertheless, despite the steady economic life, this group has a propensity to be conservative in terms of religion and politics. Moreover, their less wise usage of social media leads to low digital literacy. It is indicated by the common postings that involve ethnicity, religion, race and intergroup, hoax, and other violations. This paper is a descriptive study of the behaviors of middle class Muslims in using information technology.